The Bjorka Hacking Phenomenon on Selling Personal Data as a Digital Asset from The Perspective of Maqashid Sharia - Fageh, Achmad; Solikhawati, Anisa (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
Personal data is often used as a digital commodity tool on every digital platform such as Shopee, Link Aja, Dana, Go-jek, Grab, and so on. This study aims to find out more about the Bjorka hacking phenomenon on the sale of personal data as a digital asset from a sharia maqashid perspective. This type of research is library research , namely an assessment of library sources related to the problems discussed, especially in exploring contemporary muamalah fiqh concepts from various at-Turath books and books by local fiqh muamalah figures. as well as the West. The data sources of this research are primary and secondary. The results show that the phenomenon of selling data by Bjorka is very clear that this violates the concept of maqashid sharia in terms of dharuriyat , hajiyat , and tahsiniyat . Based on maslahah dharuriyat which is divided into 5 aspects, namely maintaining religion ( hifdhud diin ), guarding the soul ( hifdhun nafs ), guarding offspring ( hifdhud nasl ), guarding reason ( hifdhul aql ), even protecting property ( hifdhul maal ), cases of selling personal data are something that deviates from the principles of maqashid sharia.